The Effectiveness of the Communication Media of the Nurul Hayat Foundation in Increasing the Acceptance of Zakat, Infaq and Alms in Medan City - Sinaga, Mhd. Hidayatulah; Samosir, Hasrat Efendi; Zainun, Zainun (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2020)
This study aims to analyze how the effectiveness of the Nurul Hayat Foundation's communication media in increasing the receipt of zakat, infaq and alms in Medan. With the research method used is a qualitative approach, field research type (field research) which is descriptive. With primary and secondary data sources. With data collection techniques: interview (interview), observation, study literature (library research), and documentation. After the data is collected, then the data is validated through data reduction, data presentation, and drawing conclusions. The results of this study are: The communication media used by LAZ Nurul Hayat Medan City branch, namely; Application media, promotional media, and personal communication both online and not online. While the success of communication media used in increasing Zakat, Infaq and Sedaqah income at LAZ Nurul Hayat Medan City branch, namely; direct communication services, pick-up services, and services via transfer by collecting ZIS funds at Nurul Hayat Medan and through Nurul Hayat Medan Branch programs in the form of infaq or zakat pick-up service facilities, provision of transfer accounts for infaq and zakat as well as giving monthly magazines, foster parents programs, orphans, old widows, sajada programs, duafa programs, and fairy tales, as well as programs for building intimacy.